2012
DOI: 10.5194/bgd-9-11443-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internal respiration of Amazon tree stems greatly exceeds external CO<sub>2</sub> efflux

Abstract: Respiration in tree stems is an important component of forest carbon balance. The rate of CO2 efflux from the stem has often been assumed to be a measure of stem respiration. However, recent work in temperate forests has demonstrated that stem CO2 efflux can either overestimate or underestimate respiration rate, because of emission or removal of CO2 by transport in xylem water. Here we used the ratio between CO2 efflux and O2 influx in stems of tropical fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 42 publications
0
33
0
2
Order By: Relevance
“…Carbon dioxide, on the other hand, is produced in soil by cellular respiration and diffuses to the atmosphere. Thus, when only respiration and diffusion drive the concentration gradients of soil O 2 and CO 2 , a linear relationship is expected in a plot of pCO 2 versus pO 2 from different soil locations (e.g., depths or landscape positions) or sampling times (Angert et al, , ). Some processes cause CO 2 to vary, without affecting O 2 (e.g., CO 2 dissolution in water or metabolism with non‐O 2 electron acceptors, like NO 3 − ), which causes the relationship between O 2 and CO 2 to deviate from the expected linear relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon dioxide, on the other hand, is produced in soil by cellular respiration and diffuses to the atmosphere. Thus, when only respiration and diffusion drive the concentration gradients of soil O 2 and CO 2 , a linear relationship is expected in a plot of pCO 2 versus pO 2 from different soil locations (e.g., depths or landscape positions) or sampling times (Angert et al, , ). Some processes cause CO 2 to vary, without affecting O 2 (e.g., CO 2 dissolution in water or metabolism with non‐O 2 electron acceptors, like NO 3 − ), which causes the relationship between O 2 and CO 2 to deviate from the expected linear relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, some studies have shown that the ratio of soil surface CO 2 efflux to O 2 influx (a better indicator for biological activities) is around 1.0 (0.9-1.06) in various ecosystems (Seibt et al, 2004;Angert et al, 2012;Ishidoya et al, 2013). Since most soil respiration measurements have been conducted at the soil surface as CO 2 efflux, we do not differentiate soil respiration from soil surface CO 2 efflux and use the two terms loosely and interchangeably in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Angert et al (2012b) estimaron que la liberación de CO 2 equivalía a 2/3 del consumo de oxígeno, debido al reciclaje y transporte axial del CO 2 respirado. Aunque más precisa, esta técnica es también más exigente técnicamente.…”
Section: Métodos De Estimación De La Respiración Del Troncounclassified
“…Solo así se podrá seguir proporcionando información que resulte útil en la investigación de la respiración de los órganos leñosos; un tema del que se conoce muy poco, y en el que es necesario profundizar mucho más para llegar a conocer su regulación metabólica, modulación ambiental e implicaciones ecológicas. La cuantificación de la composición isotópica del carbono respirado (Ubierna et al 2009, Kuptz et al 2011, Maunoury-Danger et al 2013, Mildner et al 2014) o del oxígeno consumido (Angert et al 2012b) por el tronco o por sus componentes con tejidos vivos -cambium, floema y albura -, constituye otro paso más hacia la comprensión del proceso de la respiración leñosa.…”
Section: Métodos De Estimación De La Respiración Del Troncounclassified